Comparative expression profiles of carboxylesterase orthologous CXE14 in two closely related tea geometrid species, Ectropis obliqua Prout and Ectropis grisescens Warren - Yang, Fengshui; Li, Yujie; Gao, Mengyuan; Xia, Qing; Wang, Qian; Tang, Meijun; Zhou, Xiaogui; Guo, Huawei; Xiao, Qiang; Sun, Liang (Frontiers in Physiology, 2023)
Insect carboxylesterases (CXEs) can be expressed in multiple tissues and play crucial roles in detoxifying xenobiotic insecticides and degrading olfactory cues. Therefore, they have been considered as an important target for development of eco-friendly insect pest management strategies. Despite extensive investigation in most insect species, limited information on CXEs in sibling moth species is currently available. The Ectropis obliqua Prout and Ectropis grisescens Warren are two closely related tea geometrid species, which share the same host of tea plant but differ in geographical distribution, sex pheromone composition, and symbiotic bacteria abundance, providing an excellent mode species for studies of functional diversity of orthologous CXEs. In this study, we focused on EoblCXE14 due to its previously reported non-chemosensory organs-biased expression. First, the EoblCXE14 orthologous gene EgriCXE14 was cloned and sequence characteristics analysis showed that they share a conserved motif and phylogenetic relationship. Quantitative real-time polymerase chain reaction (qRT-PCR) was then used to compare the expression profiles between two Ectropis spp. The results showed that EoblCXE14 was predominately expressed in E. obliqua larvae, whereas EgriCXE14 was abundant in E. grisescens at multiple developmental stages. Interestingly, both orthologous CXEs were highly expressed in larval midgut, but the expression level of EoblCXE14 in E. obliqua midgut was significantly higher than that of EgriCXE14 in E. grisescens midgut. In addition, the potential effect of symbiotic bacteria Wolbachia on the CXE14 was examined. This study is the first to provide comparative expression profiles of orthologous CXE genes in two sibling geometrid moth species and the results will help further elucidate CXEs functions and identify a potential target for tea geometrid pest control.